The crimes of homicide and murder as subsequent events to a sexual crime: Regulation in the Spanish penal code after the latest reforms - Requejo Conde, Carmen (Revista de Estudios de la Justicia, 2023)
The following pages analyze the crimes against the life (homicide and murder) that follow a sexual crime in the Spanish penal code, after its drafting by Organic Law 1/2015, that made the attack on life (murder) followed by a crime against the sexual freedom of the victim a hyper-aggravated crime punishable by a reviewable permanent prison sentence, established in Spanish Law in that same year. The first section of this article describes the assumptions applied by the judges in these first eight years of validity. The relationship of this crime with the circumstance that it is a death to prevent another previous crime from being discovered, which was reintroduced on that same date as an element of murder, made the compatibility between both crimes a far from peaceful issue, on the that the Spanish judges have also ruled at this time considering that the application of the two crimes together to a single case breaks the non bis in idem principle.